Role of magnesium in major depressive disorder (Bangladesh Journal of Pharmacology, 2025)
Major depressive disorder, a common and complex disorder, has its onset associated with many factors. Common management includes antidepressant agents, together with psychotherapy in severe cases, but a significant percentage of patients do not improve. The urgency of newer approaches is a need, and clinical trials are studying the role of magnesium in depression. However, findings are inconclusive. To evaluate the evidence about the effects of magnesium on adults with depression, a systematic review was conducted. The search was conducted using scientific records from online databases between 2000 to 2023 concerning magnesium in depression. Eight studies showed mainly positive results; three studies after magnesium add-on with traditional antidepressants, and two studies showed no improvement. The review's evidence suggested that magnesium supplementation might be effective. Therefore, further clinical trials must be designed to evaluate the efficacy of magnesium alone or in addition to other therapies following biochemical assessments.